The competence approach as a tool to improve the effectiveness of personnel management of the organization (on the example of the Inter RAO Group) - S. V. Puchka (Путеводитель предпринимателя, 2020)
In this paper, the competence approach is considered as a tool to improve the efficiency of personnel management in an organization in the Russian energy holding. The author presents the results of the practical work carried out to introduce a competence approach at the enterprises of the Inter RAO Group in 2014-2016. To implement this task, the method of design decisions is used, when the program of changes includes the implementation of several consecutive projects. In support of the effectiveness of project solutions, the author presents the socio-economic results of the implementation of the program of changes.